Combination prostate cancer therapy: Prostate-specific membranes antigen targeted, pH-sensitive nanoparticles loaded with doxorubicin and tanshinone - Guanxing Sun; Kai Sun; Jie Sun (Taylor & Francis Group, 2021)
Prostate cancer is the second most frequently diagnosed cancer in the men population. Combination anticancer therapy using doxorubicin (DOX) and another extract of traditional Chinese medicine is one nano-sized drug delivery system promising to generate synergistic anticancer effects, maximize the treatment effect, and overcome multi-drug resistance. The purpose of this study is to construct a drug delivery system for the co-delivery of DOX and tanshinones (TAN). Lipid nanoparticles loaded with DOX and TAN (N-DOX/TAN) were prepared by emulsification and solvent-diffusion method. PSMA targeted nanoparticles loaded with DOX and TAN (P-N-DOX/TAN) were synthesized by conjugating a PSMA targeted ligand to N-DOX/TAN. We evaluate the performance of this system in vitro and in vivo. P-N-DOX/TAN has a size of 139.7 ± 4.1 nm and a zeta potential of 11.2 ± 1.6 mV. The drug release of DOX and TAN from P-N-DOX/TAN was much faster than that of N-DOX/TAN. N-DOX/TAN presented more inhibition effect on tumor growth than N-DOX and N-TAN, which is consistent with the synergistic results and successfully highlighting the advantages of combing the DOX and TAN in one system. P-N-DOX/TAN achieved higher uptake by LNCaP cells (58.9 ± 1.9%), highest tumor tissue distribution, and the most significant tumor inhibition efficiency. The novel nanomedicine offers great promise for the dual drug delivery to prostate cancer cells, showing the potential of synergistic combination therapy for prostate cancer.